INDUSTRIALIZATION AND FAMILY TRANSFORMATION (Annual of the Faculty of Philosophy in Skopje, 2024)
Throughout history, families have undergone significant and profound changes.From the pre-industrial era to the present day, family structures have evolved dueto industrialization, technological advancements, and shifting societal values. In thepre-industrial period, families focused on imparting essential skills to children, withwomen primarily managing household affairs and men assuming authoritative roles.However, industrialization brought about numerous changes in family life: familymembers joined the workforce, women gained prominence in public life, and traditionalgender roles shifted. The emergence of capitalism altered economic dynamics, emphasizingindividualism. Technological progress further transformed society, impacting medicine,communication, and daily life. Today, marriage rates have significantly declined,divorce rates have increased, fertility rates are lower, and marriage and childbirth arebeing postponed. This study aims to provide an overview of the characteristics and lifestylesof families before industrialization and to analyze the influence and changes infamilies brought about by the effects of industrialization.
Keywords: family; industrialization; family structure; marriage; household; fertility